Asset prices, liquidity preference, and the business cycle - Korkut A. Erturk (Levy Economics Institute of Bard College, 2001)
In his Treatise on Money, Keynes relied on two different premises to argue that the interest rate need not rise with rising levels of expenditure. One of these was the elasticity of the money supply, and the other was the interaction between financial and industrial circulation. A decrease (increase) in what Keynes called the bear position was similar in its impact to that of a policy-induced increase (decrease) in the money supply. In his General Theory, this second line of argument lost much of its force as it became reformulated under the rubric of Keynes's liquidity preference theory of interest. Assuming that the interest rate sets the return on capital, Keynes dismissed the effect of bull or bear sentiment in equity markets as a second-order complication that can be ignored in analyzing the equilibrium level of investment and output. The objective of this paper is to go back to this old theme from the Treatise and underscore its importance for the Keynesian theory of the business cycle.
Keywords: 330